2008
DOI: 10.1158/1078-0432.ccr-07-0610
|View full text |Cite
|
Sign up to set email alerts
|

Immune Function Abnormalities in Peripheral Blood Mononuclear Cell Cytokine Expression Differentiates Stages of Cutaneous T-Cell Lymphoma/Mycosis Fungoides

Abstract: Purpose: Mycosis fungoides (MF) is a cutaneous T-cell lymphoma (CTCL) characterized by neoplastic skin-homing T cells. To better understand the immunopathogenesis of MF, we analyzed the functional ability of peripheral blood mononuclear cells (PBMC) from early and late MF/CTCL patients to express cytokine genes. In late stage MF/CTCL, patients were separated into those with blood involvement (+B) and without blood involvement (−B). Experimental Design: We analyzed TH1 (interleukin 2 (IL-2), IFN-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 39 publications
(32 reference statements)
6
77
0
4
Order By: Relevance
“…Some studies have reported IL-17 mRNA and/or protein expression in situ and ex vivo, whereas others reported its absence, despite the presence of IL-22-producing Th17-like cells. 21,[57][58][59]60 The present findings offer a possible explanation for these opposing results; specifically, that the differences in frequency and severity of skin colonization and infection by SE-producing bacteria between different cohorts of patients and even within a single cohort may explain why IL-17 expression differed between these studies and between patients within a single cohort. 21,57,60 The finding that SEA induces IL-17 expression in nonmalignant primary T cells was not unexpected, given that SEA mediates STAT3 activation in these cells, 77 but it was important because it suggests that both malignant and nonmalignant T cells may contribute to IL-17 expression in vivo.…”
Section: Discussionmentioning
confidence: 67%
“…Some studies have reported IL-17 mRNA and/or protein expression in situ and ex vivo, whereas others reported its absence, despite the presence of IL-22-producing Th17-like cells. 21,[57][58][59]60 The present findings offer a possible explanation for these opposing results; specifically, that the differences in frequency and severity of skin colonization and infection by SE-producing bacteria between different cohorts of patients and even within a single cohort may explain why IL-17 expression differed between these studies and between patients within a single cohort. 21,57,60 The finding that SEA induces IL-17 expression in nonmalignant primary T cells was not unexpected, given that SEA mediates STAT3 activation in these cells, 77 but it was important because it suggests that both malignant and nonmalignant T cells may contribute to IL-17 expression in vivo.…”
Section: Discussionmentioning
confidence: 67%
“…51) and aberrant expression of IL-17. 52 In classical Hodgkin's lymphoma, HSP90 is essential for JAK/STAT signalling, as it activates JAK1 and JAK2. 53 The Ephrin family of tyrosine kinase receptors have also been shown to activate the JAK-STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…12 In the inflammatory context, cytokines that are derived from inflammatory cells play a key role in restricting immune functions and act concomitantly with suppressive inflammatory cytokines that are secreted by the tumor cells themselves. 13 Attempts to associate a unique cytokine profile with the disease based on skin or blood samples have generally indicated that a shift from Th1 to Th2 cytokine production [14][15][16][17][18] accompanies disease progression. Furthermore, Th2 cell-specific transcription factors, such as GATA-3 and JunB, were highly overexpressed in SS, as detected by cDNA microarray analysis.…”
Section: Introductionmentioning
confidence: 99%